Optical detection methods for microfluidic devices - Koepke, Marina M., author; Lear, Kevin L., advisor; Wilson, Jesse, committee member; Gustafson, Daniel, committee member (Colorado State University. Libraries, 2020)
Optical technology is a common tool integrated onto microfluidic devices to aid in data collection and counting for biological and chemical research. In this study, a simple optical technique was investigated as a detection method for microfluidic impedance cytometry (MIC) devices. The MIC devices were designed to characterize size and structure of parasite eggs through electrical impedance measurements. This data could directly benefit the medical and veterinary communities by providing information to aid in addressing helminth infections in humans and animals. The current MIC device and instrumentation does not provide a robust way to validate which impedance changes correlate to parasite eggs passing through the electrodes. To address this, an optical detection method was designed, implemented and tested on two different types of microfluidic devices: a glass device and printed circuit board (PCB) device. The optical hardware was accompanied by a trigger circuit that was used to process and manipulate the detected light signal. The circuit was designed with a sensitivity that would detect small changes in light from strongyle-type eggs flowing through the microfluidic channel. The trigger circuit was composed of multiple stages of signal amplification and oscillation suppression techniques so the changes in light could clearly be detected by the electronics. This method proved to be successful in detecting voltage changes ranging from 1.7 mV to 6.8 mV which resulted from strongyle egg sized particles (63-75 μm in diameter) flowing through the microfluidic channel. Adaptations for the optics, bench set-up and microfluidic device design were investigated to transfer this method to different laboratory settings. This study outlines the process of utilizing basic lab tools and components to create an easy to implement optical detection method for a variety of chip designs and laboratory set-ups.
Keywords: optical detection; trigger circuit; parasite detection; microfluidics